2021
DOI: 10.1175/jas-d-20-0252.1
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Layer Recovery and Precipitation Symmetrization Preceding Rapid Intensification of Tropical Cyclones under Shear

Abstract: This study investigates the precipitation symmetrization preceding rapid intensification (RI) of tropical cyclones (TCs) experiencing vertical wind shear by analyzing numerical simulations of Typhoon Mujigae (2015) with warm (CTL) and relatively cool (S1) sea surface temperatures (SSTs). A novel finding is that precipitation symmetrization is maintained by the continuous development of deep convection along the inward flank of a convective precipitation shield (CPS), especially in the downwind part. Beneath th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…Second, the diurnal pulse may represent a more symmetric convective structure (or symmetrization process) of the TC, as it is a ring‐like (symmetric) feature that manifests at the cloud top and possibly exists through the deep convective layer (Ditchek, Corbosiero, et al., 2019; Ditchek, Molinari, et al., 2019; Dunion et al., 2014, 2019). It is now widely recognized that symmetric structures of convection and precipitation within the inner core are favorable for RI (Alvey et al., 2015; Chen et al., 2020; Rogers et al., 2015; Shimada et al., 2017; Tao & Jiang, 2015). Last but not least, strong outward propagating pulses will enhance the upper‐level radial outflow, as well as subsidence in the outer TC region (Chen & Zhang, 2013; Dunion et al., 2019; Ryglicki et al., 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Second, the diurnal pulse may represent a more symmetric convective structure (or symmetrization process) of the TC, as it is a ring‐like (symmetric) feature that manifests at the cloud top and possibly exists through the deep convective layer (Ditchek, Corbosiero, et al., 2019; Ditchek, Molinari, et al., 2019; Dunion et al., 2014, 2019). It is now widely recognized that symmetric structures of convection and precipitation within the inner core are favorable for RI (Alvey et al., 2015; Chen et al., 2020; Rogers et al., 2015; Shimada et al., 2017; Tao & Jiang, 2015). Last but not least, strong outward propagating pulses will enhance the upper‐level radial outflow, as well as subsidence in the outer TC region (Chen & Zhang, 2013; Dunion et al., 2019; Ryglicki et al., 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The fourth method for vertical force decomposition that is less dependent on a local reference state can be accomplished via (Chen et al, 2021;Davies-Jones, 2003;Doswell & Markowski, 2004;Gu et al, 2019;Jeevanjee & Romps, 2015):…”
Section: Methodsmentioning
confidence: 99%
“…As a reference, the SST at the model initial time in SSTA0 is shown in Figure 1c. Previous studies showed that the reduced SST acts to retard the recovery of low‐entropy air entering the boundary layer from aloft and therefore suppress the development of convection in the upshear‐left quadrant (Chen et al., 2021; Nguyen et al., 2019). This is also the case for the simulated Lekima and will be shown in Section 3.1.…”
Section: Simulated Data and Methodsmentioning
confidence: 99%
“…The causality between the boundary layer recovery and convective strength in the upshear‐left quadrant can be explained by the “inward rebuilding” paradigm proposed by Chen et al. (2021). Specifically, the low‐ θ e boundary‐layer parcels recover their entropy when passing through the upshear‐left and upshear‐right quadrants, then being lifted in the shear‐forced downshear convergence zone, and finally develops into mature convection when returning the upshear‐left quadrant.…”
Section: Overview Of the Simulationsmentioning
confidence: 99%